2013
DOI: 10.1057/ejis.2012.27
|View full text |Cite
|
Sign up to set email alerts
|

Sympathy or strategy: social capital drivers for collaborative contributions to the IS community

Abstract: Despite growing interest in delineating the social identity of Information Systems (IS) research and the network structures of its scholarly community, little is known about how the IS community network is shaped by individual conceptions and what motivates IS researchers to engage in research collaboration. Using an exploratory theoretical framework that is based on three dimensions of social capital theory, we examined 32 years of scientific co-authorship in an international IS researcher community. We formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 34 publications
4
13
0
11
Order By: Relevance
“…We found the network did not contain one large core community of authors unlike the other information systems communities whose co-authorship networks are dominated by a core component (Trier & Molka-Danielsen, 2013;Vidgen et al, 2007;Xu & Chau, 2006). We found that the diameter of the co-authorship network was relatively small and that the clustering co-efficient was high.…”
Section: Authors and Institutional Networkmentioning
confidence: 70%
See 4 more Smart Citations
“…We found the network did not contain one large core community of authors unlike the other information systems communities whose co-authorship networks are dominated by a core component (Trier & Molka-Danielsen, 2013;Vidgen et al, 2007;Xu & Chau, 2006). We found that the diameter of the co-authorship network was relatively small and that the clustering co-efficient was high.…”
Section: Authors and Institutional Networkmentioning
confidence: 70%
“…For example, Vidgen et al (2007) used the European Conference on Information Systems (ECIS) and measured this community's network properties using a range of centrality measures for individual authors including degree, betweenness, closeness, eigenvector, flow betweenness, and structural holes. Meanwhile, Trier and Molka-Danielsen (2013) examined the IRIS community network and how individual conceptions shape it using a similar range of centrality measures to that of Vidgen et al (2007), Swar and Khan (2013), and Cucchi and Fuhrer (2007). Similarly, Xu and Chau (2006) …”
Section: Information Systems Knowledge Infrastructure Studiesmentioning
confidence: 99%
See 3 more Smart Citations